Breast cancer; awareness of breast cancer, self-breast examination and its practice in educated women - Suraj, Lisha; Kadam, Pallavi Sanjay (International Surgery Journal, 2021)
Background: The incidence of breast cancer in India is showing an increasing trend and more patients are diagnosed with breast cancer at a younger age. The prognosis of breast cancer is better when it is diagnosed at an early stage and proper treatment started early. Breast self-examination (BSE) remains as an important inexpensive tool which help in detecting any breast abnormality and diagnosing breast cancer, especially in Indian scenario. This survey was conducted among the young ladies working or studying in a tertiary care centre in Mumbai to assess the awareness about breast cancer, BSE and its practice in educated women. Methods: This is a cross sectional study conducted among 553 females studying and working in a tertiary care institute at Mumbai. A questionnaire was prepared and response was noted down and analysed statistically. Results: According to our study even the educated women working in medical institute were not completely aware of the BSE, its practice and its importance in day-to-day life. Conclusions: The awareness about breast cancer among students and staff was found to be good in this health care institute but most of them are not aware of proper method and interval of BSE. The main medium of information was audiovisual. The awareness programmes need to be more for encouraging people to do a BSE and take an early medical help.